Management by objectives: Management philosophy for prosperous tourism organizations - Todor Kralev (UTMS Journal of Economics, 2011)
In the last fifty years since the term Management by Objectives (MBO) was introduced, numerous methods, models and theories surfaced. The first segment of the paper addresses issues regarding the organizational objectives, more specifically the importance of the objectives as a basis upon which the organization is established, the possible approaches of leading a tourism organization, and how the organization should be managed by these approaches. The principal characteristic of management is to direct the leading toward achieving the predetermined objectives. The second segment of the paper discusses the MBO process, its advantages and disadvantages. The practical implementation of the MBO is also elaborated.
Keywords: 330; tourism organization; objectives; management; MBO